RASIONALITAS EKONOMI SYARIAH (KEADILAN EKONOMI DALAM ALQURAN) - Rosnani Siregar (Institut Agama Islam Negeri Padangsidimpuan, 2016)
Sharia economy has an economic system characteristics that it is own economic system, can be said to have differences with other economic systems. All facilities and infrastructure that is used to obtain the necessities of life in the world is not solely oriented to the life of the world alone but are closely related to the afterlife. While other economies; capitalist and socialist economies are solely oriented to the life of the world alone. Sharia economic rationality can be seen on the economic principles of Sharia and the basic principles of system used. Principles of Islamic Economic, are the justice and sociological value of wealth. The basic principle of Islamic banking system is profit-sharing system as an alternative.